2019
DOI: 10.1007/s11912-019-0837-8
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Natural Killer Cells as a Platform for Immunotherapy in Pediatric Cancers

Abstract: Purpose of Review We aim to review the most recent findings in the use of NK cells in childhood cancers. Recent Findings Natural killer cells are cytotoxic to tumor cells. In pediatric leukemias, adoptive transfer of NK cells can bridge children not in remission to transplant. Interleukins (IL2, IL15) can enhance NK cell function. NK cell-CAR therapy has advantages of shorter life span that lessens chronic toxicities, lower risk of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…The optimal balance between GVHD and GVL appears to be an excellent parameter to achieve long-term survival after allo-genetic stem cell transplantation. Previous study has showed that NK cells can eliminate leukemic cells, restore immunity early after stem cell transplant, while at the same time minimal graft versus host disease [15]. The use of a novel composite end point called GVHD-free progression-free survival (GPFS) was initiated in 2016 by Dr.Malard and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal balance between GVHD and GVL appears to be an excellent parameter to achieve long-term survival after allo-genetic stem cell transplantation. Previous study has showed that NK cells can eliminate leukemic cells, restore immunity early after stem cell transplant, while at the same time minimal graft versus host disease [15]. The use of a novel composite end point called GVHD-free progression-free survival (GPFS) was initiated in 2016 by Dr.Malard and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…NK activation in the tumor microenvironment can also be an essential driver for dendritic cells and T cells to be recruited into the tumor site. Moreover, NK cells can be activated via ADCC through engaging CD16 (FcγRIIIA) with monoclonal antibodies such as daratumumab for targeting multiple myeloma and T-ALL or rituximab for treating B cell non-Hodgkin lymphoma [108,109].…”
Section: Natural Killer Cell-based Therapiesmentioning
confidence: 99%
“…Oncolytic virotherapy provokes the antitumor activity of NK cells by triggering antiviral immune responses [281]. NK cell immunotherapy has shown promising effects in the treatment of childhood solid tumors such as: rhabdomyosarcoma, Ewing's sarcoma, and neuroblastoma due to prominent GVT effects both in transplant setting and in combination with antibodies [282].…”
Section: Nk Cells In Solid Tumorsmentioning
confidence: 99%